Zebu cattle fed dry distiller’s grain or cottonseed meal had greater nitrogen utilization efficiency than non-supplemented animals - Leite, Rhaony Gonçalves [UNESP]; Hoffmann, Alvair; Romanzini, Eliéder Prates [UNESP]; Delevatti, Lutti Maneck [UNESP]; Ferrari, Adriana Cristina [UNESP]; Fonseca, Natalia Vilas Boas [UNESP]; Barbero, Rondineli Pavezzi; Cardoso, Abmael Silva [UNESP]; Reis, Ricardo Andrade [UNESP] (Springer Nature, 2022)
This study evaluated intake, apparent digestibility, ruminal parameters, nitrogen balance, and microbial protein synthesis in grazing beef cattle fed a mineral mix or combination of two coproducts (cottonseed meal and dried distiller’s grains (DDG)) during the wet season. Urochloa brizantha cv. Marandu pastures were managed under continuous stocking to maintain a fixed grazing height of 25 cm using put-and-take methodology. Eight rumen cannulated Nellore steers were used to evaluate the different supplementation strategies. The experiment was composed of four treatments: (1) mineral mixed (MM; ad libitum); (2) energy-protein supplement using corn grain (energy) and cottonseed meal (protein; CS); (3) energy-protein supplement with 50% of the cottonseed meal replaced by DDG (50DDG); and (4) energy-protein supplement with 100% of the cottonseed meal replaced by DDG (100DDG). Except for MM, all supplements were supplied at a level of 0.3% of body weight (BW). A double Latin square was the experimental design performed, with eight cannulated animals, four treatments, across four experimental periods. There was a difference between dry matter and nutrient intake among treatments. The nitrogen balance was different between MM and the other treatments. There was a linear decrease in the rumen ammonia nitrogen levels under CS, 50DDG, and 100DDG. There were no treatment effects on the other parameters evaluated (P ≥ 0.10). Replacing the protein source in the supplement composition did not affect the metabolic parameters and the microbial protein synthesis. Supplementation at a rate of 0.3% BW, compared to MM supplementation, increased the nitrogen utilization efficiency in grazing cattle.
Keywords: Beef cattle; Brachiaria grassland; Corn coproducts; Metabolism; Protein synthesis